ФУНКЦІОНАЛЬНА МОДЕЛЬ ЗАБЕЗПЕЧЕННЯ ПРОФЕСІЙНОГО САМОВИЗНАЧЕННЯ УЧНІВСЬКОЇ МОЛОДІ В УМОВАХ ОСВІТНЬОГО ОКРУГУ - Морін О. Л. (World Science, 2019)
The article is devoted to the consideration of the functional model of providing professional self-determination of pupils in the conditions of the educational district. It contains a description of the organization of the respective activities of the subjects of vocational guidance activities, which is provided with all available resources of educational districts and takes place in a complex way during the periodic, extra-curricular and extracurricular subject-transformation activities, during the pre-school preparation and profile education of the students of youth. According to the author, the model proves that the professional self-determination of students in the educational district occurs as a process of purposeful and consistent self-modification of the individual, which is carried out under the influence of the vocational guidance activity of the subjects of educational districts coordinated by the only structural unit determined by them in its composition.